Assessment of Psychosocial Problems among College Students in Selected Educational Institution, Kancheepuram District, Tamil Nadu (Medico Legal Update, 2020)
Assessment of Psychosocial Problems Among College Students in Selected educational institute,Kancheepuram District, Tamil Nadu. Aim of the study is to assess the prevalence of psychosocial problemsamong college students. Objectives of the study to assess the level of psychosocial problems amongcollege students, to find out the association between the level of psychosocial problems with their selecteddemographic variables. Non experimental descriptive design used for this study. The samples were selectedby using convenient sampling 120 college students from selected educational institution. Self structureddemographic questionnaire used to assess the demographic variables and Standardised General HealthQuestionnaire (GHQ-28) used to assess the level of psychosocial problems in college students.Data collected from 01-04-2019 to 06-04-2019. The data collected from 120 college students (Girls andBoys) in the age group between 18 to 22 years in selected Educational institution. Dhanalakshmi SrinivasanEngineering College (Pooncheri), Tamil Nadu. The study result shows psychosocial problems amongcollege students 8 (6.6%) have faced somatic symptoms, 62 (51.6%) anxiety/insomnia, 97 (80.83%) socialdysfunction and 79 (65.83%) severe depression.Study shows that there was significant association between the level of psychosocial problems faced bycollege students with occupation status of parents, education status of parents, average family income andany history of mental illness (p value =